On the Effect of Aluminum on the Microstructure and Mechanical Properties of CrN Coatings deposited by HiPIMS - Guimarães,Monica Costa Rodrigues (2018)
Hard coatings are a suitable solution for increasing the lifetime of tools and components employed in different industrial applications. Coatings of transition metal nitrides have great use for tribological applications due to due to their unique mechanical properties. Although widely employed, current deposition methods such as cathodic arc evaporation produce coatings with many defects, which in turn reduce the resistance to wear, especially under severe conditions. High Power Impulse Magnetron Sputtering is a novel physical vapor deposition technique that produces homogeneous coatings. In this study, CrN and CrAlN monolayer coatings were deposited on AISI 304 stainless steel substrates using HiPIMS. X-Ray Diffraction, Scanning Electron Microscopy, Atomic Force Microscopy were used to evaluate the microstructure, phase composition, morphology and chemical composition of the coating. Results showed that HiPIMS is a promising technique to deposit CrN and CrAlN homogeneous coatings with high hardness and good adhesion to the substrate.